2006
DOI: 10.1002/bdd.513
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a flip‐flop phenomenon in acamprosate pharmacokinetics: an in vivo study in rats

Abstract: The pharmacokinetics of acamprosate were examined in the rat after oral and intravenous administration in order to detect the possible presence of a flip-flop phenomenon. Rats received 9.3 or 73.3 mg/kg of the drug as an intravenous bolus. The same doses were orally administered via gastric intubation. Plasma samples were taken from the jugular vein for determination of acamprosate concentration by liquid scintillation counting. The drug content was also quantified in urine and faeces. The acamprosate bioavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
3
16
0
2
Order By: Relevance
“…Among factors for the acamprosate's suboptimal efficacy at low doses is the poor intestinal absorption observed in both humans (11%) (Saivin et al 1998) and rodents (20%) (Zornoza et al 2006) as well as considerably faster elimination rate compared to its absorption rate (Zornoza et al 2006). The poor intestinal absorption and the slow absorption rate stem in part from the passive diffusion as being the main route for the intestinal absorption of the drug (Mas-Serrano et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Among factors for the acamprosate's suboptimal efficacy at low doses is the poor intestinal absorption observed in both humans (11%) (Saivin et al 1998) and rodents (20%) (Zornoza et al 2006) as well as considerably faster elimination rate compared to its absorption rate (Zornoza et al 2006). The poor intestinal absorption and the slow absorption rate stem in part from the passive diffusion as being the main route for the intestinal absorption of the drug (Mas-Serrano et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This "flip-flop" phenomenon has been observed with multiple drugs; for instance, Zornoza et al (2006) observed it with acamprosate. Acamprosate (calcium bis acetylhomotaurine) is a drug used to prevent relapse in patients with alcohol (ethanol) dependence.…”
Section: Pharmacokinetics Of Oral Administrationmentioning
confidence: 90%
“…It can be observed from Fig. 13.8 that acamprosate after IV bolus and oral administration of 9.3 mg/kg follows flip-flop kinetics since the terminal slope in the oral curve is lower than the slope observed in the IV curve (Zornoza et al, 2006). This indicates that the real rate-limiting step is related to acamprosate absorption.…”
Section: Pharmacokinetics Of Oral Administrationmentioning
confidence: 95%
“…Several studies reported a slow intestinal absorption of acamprosate (Más-Serrano et al, 2000;Zornoza et al, 2002Zornoza et al, , 2004. Zornoza et al (2006) reported that the acamprosate absorption rate is considerably slower than its elimination rate so that the drug exhibits flip-flop pharmacokinetics after oral administration in rats. Therefore, based on its aqueous solubility and intestinal permeability, acamproate is a biopharmaceutics classification system (BCS) Class III drug, as it is highly soluble with low permeability (Amidon et al, 1995).…”
Section: In Vivo Release Studymentioning
confidence: 99%
“…In addition, there has been little pharmaceutical research aimed at improving acamprosate bioavailability. Most pharmacokinetic studies were carried out using drug solutions (Más-Serrano et al, 2000;Zornoza et al, 2002Zornoza et al, , 2004Zornoza et al, , 2006Courtyn et al, 2004), and no studies have been reported to date regarding the properties of enteric-coated acamprosate tablets.…”
Section: Introductionmentioning
confidence: 99%